# 7[3-7(x-1)]+7[(4x+3)-5]=13x-341

## Simple and best practice solution for 7[3-7(x-1)]+7[(4x+3)-5]=13x-341 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 7[3-7(x-1)]+7[(4x+3)-5]=13x-341 equation:

Simplifying
7[3 + -7(x + -1)] + 7[(4x + 3) + -5] = 13x + -341
Reorder the terms:
7[3 + -7(-1 + x)] + 7[(4x + 3) + -5] = 13x + -341
7[3 + (-1 * -7 + x * -7)] + 7[(4x + 3) + -5] = 13x + -341
7[3 + (7 + -7x)] + 7[(4x + 3) + -5] = 13x + -341
Combine like terms: 3 + 7 = 10
7[10 + -7x] + 7[(4x + 3) + -5] = 13x + -341
[10 * 7 + -7x * 7] + 7[(4x + 3) + -5] = 13x + -341
[70 + -49x] + 7[(4x + 3) + -5] = 13x + -341
Reorder the terms:
70 + -49x + 7[(3 + 4x) + -5] = 13x + -341
Remove parenthesis around (3 + 4x)
70 + -49x + 7[3 + 4x + -5] = 13x + -341
Reorder the terms:
70 + -49x + 7[3 + -5 + 4x] = 13x + -341
Combine like terms: 3 + -5 = -2
70 + -49x + 7[-2 + 4x] = 13x + -341
70 + -49x + [-2 * 7 + 4x * 7] = 13x + -341
70 + -49x + [-14 + 28x] = 13x + -341
Reorder the terms:
70 + -14 + -49x + 28x = 13x + -341
Combine like terms: 70 + -14 = 56
56 + -49x + 28x = 13x + -341
Combine like terms: -49x + 28x = -21x
56 + -21x = 13x + -341
Reorder the terms:
56 + -21x = -341 + 13x
Solving
56 + -21x = -341 + 13x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13x' to each side of the equation.
56 + -21x + -13x = -341 + 13x + -13x
Combine like terms: -21x + -13x = -34x
56 + -34x = -341 + 13x + -13x
Combine like terms: 13x + -13x = 0
56 + -34x = -341 + 0
56 + -34x = -341
Add '-56' to each side of the equation.
56 + -56 + -34x = -341 + -56
Combine like terms: 56 + -56 = 0
0 + -34x = -341 + -56
-34x = -341 + -56
Combine like terms: -341 + -56 = -397
-34x = -397
Divide each side by '-34'.
x = 11.67647059
Simplifying
x = 11.67647059